Impact of US dollar exchange rate and inflation on profitability - Azmi, Andri; Adam, Mohamad; Widiyanti, Marlina; Malinda, Shelfi (International research journal of management, IT and social sciences, 2022)
This study aims to examine the significance of the effect of the dollar exchange rate and inflation on the profitability of PT. Pupuk Sriwidjaja Palembang. Profitability in this study is measured by return on assets (ROA) with the research period from 2014-2020. The data analysis technique for testing the hypothesis in this study used multiple linear regression. The study results concluded that the dollar exchange rate and inflation had a significant positive effect on the profitability (ROA) of PT. Pupuk Sriwidjaja Palembang during 2014-2020.